2017
DOI: 10.15296/ijwhr.2018.38
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Leiomyosarcoma: A Case Report

Abstract: Introduction: Uterine leiomyosarcoma (LMS) is a rare cancer originated from smooth muscle lining the walls of the uterus. LMS is known as an aggressive tumor with high mortality and morbidity rates as compared to other uterine cancers, despite the disease stage at the time of diagnosis. In most cases, LMS has been misdiagnosed as a benign uterine leiomyoma following hysterectomy or myomectomy. Case Presentation: We presented a 53-year-old G7 L7 woman who had referred to GYN clinic in Amir-al-Momenin hospital f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…It was found that 81 (81%) of the women had successful medical abortion and 19 women underwent suction curettage. In a rando-mized, controlled trial designed to compare the methotrexate/misoprostol vs. a more standard approach for termination of pregnancies, the mean interval to the end point in the methotrexate/misoprostol group was higher (26.4 days vs. 4.5 days, p<0.0001) [24] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that 81 (81%) of the women had successful medical abortion and 19 women underwent suction curettage. In a rando-mized, controlled trial designed to compare the methotrexate/misoprostol vs. a more standard approach for termination of pregnancies, the mean interval to the end point in the methotrexate/misoprostol group was higher (26.4 days vs. 4.5 days, p<0.0001) [24] .…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Rudasari et al, [24] in Mashhad (2004Mashhad ( -2006 on 100 pregnant women at their first trimester, the effect of Methotrexate and Misoprostol on the success rate of abortion was investigated. It was found that 81 (81%) of the women had successful medical abortion and 19 women underwent suction curettage.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Rudasari et al in Mashhad (2004Mashhad ( -2006 on 100 pregnant women at their first trimester, the effect of Methotrexate and Misoprostol on the success rate of abortion was investigated. It was found that 81 (81%) of the women had successful medical abortion and 19 women underwent suction curettage (16).…”
Section: Discussionmentioning
confidence: 99%
“…LMS is usually diagnosed following the surgery , although in rare conditions, a frozen section is used during the surgery. 6 In most cases, the diagnosis of LMS is made by pathological examination of hysterectomy or myomectomy specimen. 5 Here we present an extremely rare case of uterine LMS coexisting with endometrial endometrioid adenocarcinoma of the uterus.…”
mentioning
confidence: 99%